Potential vestibular pathway impairment in children with recurrent vertigo: An investigation through air-conducted sound and galvanic vestibular stimulation-triggered vestibular evoked myogenic potentials - Sun, Xiayu; Gao, Dekun; Shen, Jiali; Zhu, Qi; Wang, Lu; Ma, Xiaobao; Wang, Wei; Chen, Xiangping; Zhang, Qing; Jin, Yulian; Chen, Jianyong; Yang, Jun (Frontiers in Neurology, 2022)
Objective This study aims to investigate the potential vestibular pathway impairment through vestibular evoked myogenic potentials (VEMPs) and to explore the pathophysiological significance of these instrument-based findings in children with recurrent vertigo. Materials and methods The clinical data of 21 children (mean age 4.67 ± 1.39 years) diagnosed as RVC who met the inclusion criteria of the Bárány Society and 29 healthy children (mean age 4.83 ± 1.34 years) enrolled as the control group from February 2021 to December 2021 were collected and analyzed retrospectively. All the subjects underwent both cervical VEMP (cVEMP) and ocular VEMP (oVEMP) triggered by air-conducted sound (ACS) and galvanic vestibular stimulation (GVS), respectively. The elicit rate, latency, and amplitude asymmetry ratio (AAR) of ACS-cVEMP, ACS-oVEMP, GVS-cVEMP, and GVS-oVEMP were analyzed. Results (1) The elicit rates of ACS-cVEMP and ACS-oVEMP were similar in the two groups (P > 0.05), as well as GVS-cVEMP and GVS-oVEMP (P > 0.05). (2) P1 and N1 latencies of ACS-cVEMP and GVS-cVEMP in the RVC group were longer than those in the control group (P < 0.05). (3) The N1 latency of ACS-oVEMP in the RVC group was shorter than that in the control group (P < 0.05), while there was no significant difference in the P1 latency of ACS-oVEMP (P > 0.05). The N1 and P1 latencies of GVS-oVEMP were not significantly different (P > 0.05). (4) There was no statistical difference in the AAR of ACS-cVEMP and GVS-cVEMP. Although there was an increased AAR of ACS-oVEMP in the RVC group (P < 0.05), the AAR was within the normal range. However, no statistical difference was found in the AAR of GVS-oVEMP in the two groups (P > 0.05). Conclusion The latencies of ACS-cVEMP and GVS-cVEMP in children with recurrent vertigo were significantly prolonged compared with those in healthy children, and there was no difference in elicit rates of ACS-cVEMP and GVS-cVEMP, suggesting that there might be potential impairment in the inferior vestibular nerve and the subsequent nerve conduction pathway in RVC.